THE INFLUENCE OF MOTIVATION AND ACHIEVEMENT IN SENIOR HIGH SCHOOL - Denarti, Rizki; Damayanti, Ika Lestari (Premise: Journal of English Education and Applied Linguistics, 2023)
This study aims to investigate the kind of students' motivation in studying English, whether they had intrinsic or extrinsic motivation, and to explore what kind of motivation would impact students with higher scores in their achievement. Using random sampling, this study employed 53 first-grade students from the population of 324 from Senior High School in Bengkulu. Data was collected using a questionnaire and analyzed using Likert Scale, descriptive statistics, and Pearson Correlation in SPSS. The results showed that the students have intrinsic and extrinsic motivation in learning English, with a total mean score of intrinsic motivation of 4.14 and extrinsic motivation of 3.87, and they are categorized as having high levels of motivation. However, when the data was correlated with motivation, it was shown that intrinsic motivation has a weak correlation (r= 0,327) with achievement; meanwhile, extrinsic motivation does not relate. From this finding, the researcher would state that motivation does not significantly impact students with higher achievement.